Research progress of MUC1 in genitourinary cancers - Weipu Mao; Houliang Zhang; Keyi Wang; Jiang Geng; Jianping Wu (Cellular & Molecular Biology Letters)
Abstract MUC1 is a highly glycosylated transmembrane protein with a high molecular weight. It plays a role in lubricating and protecting mucosal epithelium, participates in epithelial cell renewal and differentiation, and regulates cell adhesion, signal transduction, and immune response. MUC1 is expressed in both normal and malignant epithelial cells, and plays an important role in the diagnosis, prognosis prediction and clinical monitoring of a variety of tumors and is expected to be a new therapeutic target. This article reviews the structural features, expression regulation mechanism, and research progress of MUC1 in the development of genitourinary cancers and its clinical applications.